The maintenance of sexually antagonistic variation in reproductive success by negative frequency-dependence in the bank vole (Myodes glareolus) - Martiskainen, Henna (2011)
Natural selection theory predicts low variance in traits closely related to reproductive success, since the most fit trait value should replace all the others. However, a considerable amount of variation is found in life-history traits throughout the animal kingdom. The most widely accepted mechanism maintaining this variation is a balance between mutation and selection; however, observed variance is higher than predicted by mutation – selection balance alone and thus additional processes must be involved. One possible mechanism which has only recently started to gain attention is intralocus sexual conflict, where the optima of fitness related traits are sex dependent. This leads to sexually antagonistic variation in life-history traits, especially those related to reproduction where the sexes diverge most. Intralocus conflict alone might only be able to slow down the depletion of variation, but become really powerful when combined with negative frequency-dependent selection, which favors the rare morphs in the population. In my master ‟s thesis I investigate the interaction between these two selective forces, sexually antagonistic selection and frequency-dependent selection, and their potential to maintain variation in life- history traits. Bank voles (Myodes glareolus) were artificially selected in the laboratory according to sexually antagonistic selection to create two lines with opposing reproductive success (high-dominance males with low- fecundity sisters and vice versa). I found a significant difference between the lines in male dominance in behavioral laboratory trials and plasma testosterone levels. The frequency of these two lines was then manipulated in semi- natural field enclosures to be either rare or common in the population. Reproductive success was measured by observing female litter size and determining male siring success with genetic paternity analysis. Reproductive success of males in the field was negatively frequency-dependent regardless of their selected dominance status, whereas in females only the selected fecundity status explained their reproductive success. The results of my thesis suggest that the negative frequency-dependence experienced by male bank voles could maintain sexually antagonistic variation in this species by a cyclic fluctuation in the frequency of the different (male) tactics.